2002
DOI: 10.4314/sajas.v32i1.3789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Charolais and Hereford sires and straightbred and crossbred dams on pre-weaning growth of calves

Abstract: Weaning performance of calves sired by Charolais and Hereford on dams of Angus, Bonsmara and Hereford and various crossbred dam combinations was compared. Charolais sired calves were on average 5 kg heavier at birth and 20 kg heavier at weaning than Hereford sired calves. Among the three straightbred dam breeds, the Bonsmara weaned calves that were approximately 6% heavier than both the Angus and the Hereford calves. The use of crossbred dams having intermediate levels of Charolais composition is suggested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
6
14
0
Order By: Relevance
“…Calves of Beef Simmental, Charolais, AA and Blonde d'Aquitaine showed a great potential for growth intensity traits. These findings were in agreement with results reported by Dymnicki et al (1996) and Dadi et al (2002). Similarly, Jakubec et al (2003) reported high weights and average daily gains for Blonde d'Aquitaine, Charolais and BS calves that were higher in comparison with calves raised in Slovakia (except for birth weights).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Calves of Beef Simmental, Charolais, AA and Blonde d'Aquitaine showed a great potential for growth intensity traits. These findings were in agreement with results reported by Dymnicki et al (1996) and Dadi et al (2002). Similarly, Jakubec et al (2003) reported high weights and average daily gains for Blonde d'Aquitaine, Charolais and BS calves that were higher in comparison with calves raised in Slovakia (except for birth weights).…”
Section: Discussionsupporting
confidence: 92%
“…The results are in accordance with findings of Dadi et al (2002) and Goyache et al (2003), who analysed growth traits of beef calves raised in South Africa and Spain, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Van Zyl (1990) and Meaker (1993) reported differences (P < 0.05) in weaning weight between Simmentaler, Bonsmara and AF calves. The results obtained by Dadi et al (2002a) that larger-framed Charolais-sired calves were heavier (P < 0.001) at birth (38.4 vs. 33.4) and weaning (197.1 vs. 177.5) than the smaller-framed Hereford-sired calves, supported the results observed in the present study. These authors also indicated that Bonsmara cows gave birth to and weaned heavier calves (P < 0.05) than Hereford and Angus cows.…”
Section: Discussionsupporting
confidence: 91%
“…Dillard et al (1980) concluded that the lower weight at weaning reached by crossbreds from HE dams was probably due to the fact that HE dams did not have enough milk and maternal ability to maximise the growth of calves, crossed with Charolais. Dadi et al (2002) found that most crossbred calves from HE dams were characterised by lower body weight at weaning compared to those from dams of other breeds. The negative effect of Hereford cows was also demonstrated by Skrypzeck et al (2000).…”
Section: Discussionmentioning
confidence: 97%
“…Compared to the CH bulls, the CH × SI bulls reached more than 5% higher weight at weaning and daily gains from birth to weaning, while these traits were lower in the CH × HE crossbreds by 9% and 11%, respectively. Nearly all comparable studies reported a negative direct maternal effect of the HE dam on the body weight at weaning of the progeny (Alenda et al, 1980;Franke et al, 2001, Dadi et al, 2002. Dillard et al (1980) concluded that the lower weight at weaning reached by crossbreds from HE dams was probably due to the fact that HE dams did not have enough milk and maternal ability to maximise the growth of calves, crossed with Charolais.…”
Section: Discussionmentioning
confidence: 99%